PHYTOCHEMICAL AND PHARMACOLOGICAL EVALUATION OF ANDROGRAPHIS PANICULATA AND VITEX NEGUNDO FOR ANALGESIC ACTIVITY - SEN, DIVYA; SAHU, MANOJ; VERMA, LOKESH; BANWEER, JITENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Pain is defined physical or mental depending on it source of origin and pain treated with anti-anxiety, antidepressant, and analgesic medicine. Andrographis paniculata locally called kalmegh of Acanthaceae family and Vitex negundo locally called nirgundi of Lamiaceae, both medicinal plants which yield the therapeutic compound and herbal drug used cure diseases. Methods: The analgesic activity was performed by hot plat and tail immersion method. The present study extract performs models plants 50 Swiss albino mice four groups of each five animals. This experimental animal administered with extract intraperitoneal at dose level 50, 100, and 300 mg/kg used as reference drugs diclofenac sodium-induced time test using albino mice as experimental animal. Results: Medicinal plants ethanolic extract contains reducing carbohydrate, flavonoids, tannins, and triterpenoids. The sample comparable antibacterial cytotoxic activity. The different solvent soluble and mild activity herbal drug analgesic highest activity compared to standard drug, diclofenac sodium. Conclusion: Analgesic models based different parameter for studies bioactive compounds further for isolation and purification compounds.